STRATEGI IFAW (INTERNATIONAL FUND FOR ANIMAL WELFARE) MENGHENTIKAN PERBURUAN PAUS KOMERSIAL DI ISLANDIA TAHUN 2010-2017 - Nanditya Wardhana, I Gusti Agung; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Uncontrolled whaling is an international issue. This causes a reduction in the world's whale population. Most whale populations in the world are spent by whale hunters. Iceland is a country that still engages in commercial whaling until now even though it has become a member of the IWC. The IWC as a whaling regulation organization is unable to stop commercial whaling by Iceland. This inability led to other international organizations that took part in efforts to stop commercial whaling in Iceland, one of which was IFAW. In an effort to stop whaling commercially in Iceland, IFAW has several strategies. This study aims to find out how the IFAW (International Fund for Animal Welfare) strategy stopped commercial whaling in Iceland in 2010-2017. The concept used in this study refers to the ENGO strategy proposed by Rieteg. This study uses descriptive qualitative methods. The analysis technique used is descriptive qualitative by describing the results of the study in narrative form. The results showed that there were two strategies that IFAW could use in its efforts to stop whaling in Iceland, namely outsider strategy and insider strategy. The outsider strategy was carried out with the Meet Us Don't Eat Us campaign and used international pressure to urge Iceland's commercial whaling policy to be stopped. Meanwhile, the insider strategy was carried out with IFAW's collaboration with local politicians and cooperation with the UK in the IWC meeting to reveal vote buying.   Keyword: IFAW, Insider Strategy, Outsider Strategy, Whaling